ANALISIS KANDUNGAN SEDIMEN DAN HARA TERANGKUT PADA DAS SUMPUR KABUPATEN TANAH DATAR - Yulnafatmawita Yulnafatmawita; Amrizal Saidi; Aulia Rahman (Jurnal Solum, 2010)
A study about sediment content and nutrient movement was conducted in Sumpur watershed, Tanah Datar Regency, West Sumatra. The objective of the research was to determine sediment content and nutrient movement on Sumpur watershed and the relationship. Survey method by sampling water in joining river was employed to this research for sampling water. Water was sampled exactly after rain or at the time of river debit was maximum and without rain as a control. Water flowing into the river comes from several lad uses in the upper watershed. There were four types of land use found in the areas, those were forest, mixed garden, annual season crops, and rice field. Based on field observation it was found that there were two classes of soils there, Andisols and Inceptisols. The results of laboratory analyses showed that river current, soil consentration in river water, as well as sediment content were linearly correlated to rainfall amount. Positive linear correlation was also found between river debit and carried nutrients (N, P, K, Ca, Mg, Na) from the research area. Keywords: watershed, rainfall, sediment carried, and nutrient carried